2007
DOI: 10.1097/01.tp.0000275377.09660.fa
|View full text |Cite
|
Sign up to set email alerts
|

Late Recurrent Urinary Tract Infections May Produce Renal Allograft Scarring Even in the Absence of Symptoms or Vesicoureteric Reflux

Abstract: In patients with late UTIs, renal scarring is a frequent finding. Scarring may occur even in asymptomatic patients without VUR. The lack of an effect on graft survival may reflect successful intervention with prophylactic antibiotics and surveillance urine cultures. Late recurrent UTIs may be damaging to renal allografts, even in the absence of reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 23 publications
5
63
2
5
Order By: Relevance
“…the findings from some studies have shown that GPN induces graft dysfunction (Giral et al 2002;Pelle et al 2007), the mechanism of graft dysfunction following GPN has not been clarified. The finding from one study suggested GPN could cause interstitial scars in renal allografts and a subsequent reduction in the functional nephron mass (Dupont et al 2007). On the other hand, bacterial infection is also likely to induce the activation of the immune system, leading to acute or chronic rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the findings from some studies have shown that GPN induces graft dysfunction (Giral et al 2002;Pelle et al 2007), the mechanism of graft dysfunction following GPN has not been clarified. The finding from one study suggested GPN could cause interstitial scars in renal allografts and a subsequent reduction in the functional nephron mass (Dupont et al 2007). On the other hand, bacterial infection is also likely to induce the activation of the immune system, leading to acute or chronic rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from some studies have shown that GPN is associated with interstitial scarring in renal allografts (Dupont et al 2007) and that it can activate an alloimmune response to the donor organ and subsequently contribute to acute or chronic rejection (Audard et al 2005;Locke et al 2009). In a previous cohort study, the occurrence of early-onset GPN following kidney transplantation was significantly associated with increased rates of renal allograft loss (Giral et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, UTIs are frequent after renal transplantations (16) and may adversely impact renal allograft function, even in the absence of VUR (37,38). Dupont et al (32) evaluated whether the presence of VUR confers an increased risk for UTIs and renal allograft scarring.…”
Section: Discussionmentioning
confidence: 99%
“…В первый месяц после трансплантации почки у 50-70% реципиентов развиваются инфекции мочевы-водящих путей [5,7], оказывающие непосредственное влияние на функциональную состоятельность транс-плантата [15]. Частота инфекции мочевой системы составляет около 65,4% у больных с урологическими осложнениями после трансплантации и 40,7% -у па-циентов без урологических проблем.…”
unclassified